MANAJEMEN TATA KELOLA BISNIS RASULULLAH SAW - A. M. Luthfi Virgiawan; Rahmatullah; Supriadi; Mukhtat Lutfi (LPPM STAI Muhammadiyah Probolinggo, 2026)
The Prophet Muhammad SAW is recognized not only as a religious figure but also as a great entrepreneur and business leader whose principles remain relevant in the modern world. This study aims to explore the concept of business governance management in the life of the Prophet Muhammad SAW, covering aspects of honesty (shiddiq), trustworthiness (amanah), communication (tabligh), and intelligence (fathanah) as foundational values in building ethical and sustainable businesses. Using a qualitative approach through library research, this study examines various sources of hadith, historical accounts, and contemporary Islamic economic literature. The findings indicate that the Prophet Muhammad SAW applied management principles that align with modern concepts of good corporate governance, including transparency, accountability, responsibility, fairness, and stakeholder independence. Furthermore, the Prophet's business model emphasizes social justice, prohibition of usury (riba), and partnership-based profit sharing. These principles offer an alternative management framework that integrates spiritual values with economic rationality, and are relevant for developing Islamic economics and ethical business management in the contemporary era.